A Decade of Respiratory Syncytial Virus Epidemiology and Prophylaxis: Translating Evidence into Everyday Clinical Practice. Issue 2 (2011) - Paes, Bosco A; Mitchell, Ian; Banerji, Anna; Lanctôt, Krista L; Langley, Joanne M
Abstract : Respiratory syncytial virus (RSV) is a common infection in infancy, with nearly all children affected by two years of age. Approximately 0.5% to 2.0% of all children are hospitalized with lower respiratory tract disease, of which 50% to 90% have bronchiolitis and 5% to 40% have pneumonia. Morbidity and mortality are highest in children with nosocomial infection and in those with underlying medical illnesses such as cardiac and chronic lung disease. Aboriginal children residing in remote northern regions are specifically considered to be at high risk for hospitalization due to RSV infection. Thorough hand washing and health education are the principal strategies in primary prevention. In the absence of a vaccine, palivizumab prophylaxis is currently the best intervention to reduce the burden of illness and RSV-related hospitalization in high-risk children. Health care professionals should provide palivizumab prophylaxis cost effectively in accordance with recommendations issued by pediatric societies and national advisory bodies. The present article reviews the epidemiology of RSV infection and the short- and long-term impact of disease in high-risk infants and special populations. Prevention strategies and treatment are discussed based on the existing scientific evidence, and future challenges in the management of RSV infection are addressed.